Technological Trends in Indian Accounting System-Its Impact on Business Management - Ganguly, P; Khandelwal, S; Maheshwari, R (International Journal of Computer Sciences and Engineering, 2025)
This research paper focuses on recent technological development and in Indian Accounting System. The emerging scenario of accounting system should not be restricted to the traditional accounting system, rather it should incorporate E-Commerce and other software based accounting curriculum. This research paper presents an analysis of Technological Impact of Indian Accounting System on the managing business process. This advance and technical accounting knowledge and skills can make all professional in current scenario. The present paper is based on Accounting System as a whole is still in need to reform so that it is proved to be more effective in reducing unemployment and to face the present challenges of global economy in the field of business and industry.